2016
DOI: 10.1515/mms-2016-0044
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Short-Circuit Effects on Transformer Winding with SFRA Method and Impact Test

Abstract: The paper presents theoretical and experimental analyses of a possible effect of the short-circuit forces on the transformer winding. The first part of the paper is focused on creation and activity of the radial and axial forces during a short circuit. It shows dimensions, direction and − of course − the resulting mechanical stress. The presented equation shows basic dependencies of these mechanical forces created in the transformer winding. Finally, the paper presents experimental methods of diagnosing and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Dominant frequency range of SFRA due to short circuit fault from bibliography survey References Dominant frequency range (Hz) [11] Devadiga et al 2018Low and medium frequency (Significant reduction in impedance and a shift in resonance peaks towards high frequencies)[12] M.Gutten, Richard Janura, Milan Sebok, DanielKorenciak, 2016 Low to medium frequencies (up to 100kHz)[13] Aljohani & Abu-Siada, 2015High levels of SC have a visible impact along the entire frequency range and influence the resonance frequencies in high frequency range.…”
mentioning
confidence: 99%
“…Dominant frequency range of SFRA due to short circuit fault from bibliography survey References Dominant frequency range (Hz) [11] Devadiga et al 2018Low and medium frequency (Significant reduction in impedance and a shift in resonance peaks towards high frequencies)[12] M.Gutten, Richard Janura, Milan Sebok, DanielKorenciak, 2016 Low to medium frequencies (up to 100kHz)[13] Aljohani & Abu-Siada, 2015High levels of SC have a visible impact along the entire frequency range and influence the resonance frequencies in high frequency range.…”
mentioning
confidence: 99%
“…From the above and using Table 1 Performance of the alarm transmission system, one of the main indicators of system reliability, is influenced by several indicators aimed at the signal transmission. Those indicators could include, for example, message transmission time, connection/connection monitoring, monitoring of the individual parts of the alarm transmission system functioning [4].…”
Section: Methodsmentioning
confidence: 99%
“…In [7], the authors used driving-point impedance for transformer parameter estimation. In [5,[12][13][14][16][17][18][19][20], SFRA data was used to detect the deformation or fault of a power transformer. The core diagnosis based on SFRA was covered in [5].…”
Section: Introductionmentioning
confidence: 99%
“…In [12], the authors first observed the relationships between parameters and frequency response and then analyzed frequency response in fault conditions. In [13,14,17,19], the SFRA was used to diagnose interturn faults such as short-circuit faults and winding deformation. The authors of [21] presented a comprehensive, detailed review of the transformer FRA, including test methods, objectives, structures, and results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation